Zhou Enlai : the last perfect revolutionary : a biography - 高, 文謙; Rand, Peter; Sullivan, Lawrence R. (PublicAffairs, 2007)
When Gao Wenqian first published this groundbreaking, provocative biography in Hong Kong, it was immediately banned in the People's Republic. Using classified documents spirited out of the China, he offers an objective human portrait of the real Zhou Enlai, the premier of the People's Republic of China from 1949 until his death in 1976. Often touted as "the last perfect revolutionary," Zhou is "a modern saint" who offered protection to his people during the Cultural Revolution, and an icon who allows modern Chinese to find an admirable figure in what was a traumatic and bloody era. But his greatest gift was to survive, at almost any price, thanks to his acute understanding of where political power resided at any one time.